Notas agudas: aspectos acústicos em tenores eruditos - Ambros, Gustavo do Amaral (2024)
Introduction: emitting high notes poses technical challenges for singers, regardless of the musical genre, as they require adaptations of the vocal tract structures. Tenors performing in operas face the challenge of producing their high notes without the aid of electronic equipment for amplification while maintaining the desired vocal quality. Considering the acoustic aspects, the theory of nonlinear source-filter interaction suggests that modifying the positioning of articulators and adjusting resonances in relation to the harmonics of the glottal source is necessary for emitting these notes. Objective: to describe acoustically the adjustments of the supraglottal vocal tract and the characteristics of the radiated spectrum of the highest notes in the tessitura of classical tenors. Method: the intentional sample consisted of five professional tenors active in operas. Sound emissions were recorded in a professionally treated recording studio. The emissions captured included: spontaneous speech; vowels /a/, /e/, /i/, /o/, and /u/ spoken in carrier sentences; performance of an excerpt of an opera aria; vocalization of two ascending eight-tone scales. Recordings were analyzed using the open-source software Praat version 6.2.23 and Sopran version 1.0.28, and the following were extracted: frequencies of the first two formants; amplitude of the first four harmonics and of the peak in the singer's formant region (between 2.5 and 3.5 kHz), sound pressure level, and long-term average spectrum. Results: the formants of the different vowel configurations varied along the scale. The first formant of vowels /e/ and /i/ tended to rise, and the second to fall; for vowels /o/ and /u/, both tended to rise. The vowel spaces of all subjects reduced from spoken voice to sung voice, and from low to high notes. In the passaggio zone, the tuning of the first formant with the second harmonic, and the second formant with the fourth harmonic was more frequent; above the passaggio, tuning of the second formant with the third harmonic was observed. No relationship was identified between formant tuning and the sound pressure level of the utterances. In all subjects, the sound pressure level was higher in the sung voice. In the long-term average spectra, all subjects exhibited the singer's formant and showed a less pronounced spectral slope in the sung voice. Conclusion: convergence of the frequencies of the first two formants in all vowels across the scale was observed, suggesting the need for articulatory adjustments for the production of high notes by classical tenors. The necessity of a specific formant adjustment maneuver in relation to the harmonics for emitting high notes was not identified; instead, different solutions were employed. Tuning of the second formant to the third harmonic was mainly used to manage the passaggio zone, while at the top of the scale, a more balanced distribution of energy among the lower partials was observed. These findings indicate the need for different resonance adjustments along the high tessitura of classical tenors